Speech and Surgical Outcomes in Children With Veau Types III and IV Cleft Palate: A Comparison of Internationally Adopted and Nonadopted Children. (March 2018) - Pet, Mitchell A.; Dodge, Ryan; Siebold, Babette; Kinter, Sara; Perkins, Jonathan; Tse, Raymond W.
Objective: This study compares speech and surgical outcomes in internationally adopted and nonadopted patients undergoing cleft palate repair, and examines the influence of age at initial palatoplasty. Design: Retrospective cohort study setting: Tertiary Care Children's Hospital. Patients: 70 international adoptees and 211 nonadoptees with Veau type III and IV clefts (without associated syndrome) repaired at our institution. Outcome Measures: Outcomes included VPI, compensatory misarticulations, intelligibility, nasal air emission, oronasal fistula, and secondary speech surgery. Speech evaluations completed near 5 years of age were gathered from a prospectively collected database. Results: Adoptees underwent palatoplasty 5.2 months after arrival, a mean of 10.4 months later than nonadoptees. Adoptees were significantly more likely to develop moderate/severe VPI and trended toward more frequent need for secondary speech surgery. Oronasal fistula occurred at similar rates. Increased age at initial palatoplasty was a significant predictor of moderate to severe VPI, and need for secondary speech surgery. Conclusions: International adoptees undergo palatoplasty 10.4 months later than nonadoptees and are significantly more likely to develop moderate/severe VPI, with a trend toward increased secondary speech surgery. An association between treatment delay and moderate/severe VPI and secondary speech surgery has been demonstrated. While a causal relationship between delayed repair and inferior outcomes in international adoptees has not been proven, this data suggests that surgical intervention upon unrepaired cleft palates soon after adoption may be beneficial. The opportunity for a change in practice exists, as half of the 10.4-month relative delay in palate repair occurs postadoption.